Development of Artificial Intelligence in Serbia. Serbia as the Regional Leader - Badža, Stefan (Napredak, 2024)
Artificial intelligence (AI) is transforming industries and social spheres, and Serbia has come forward as the leader in Southeast Europe. By adopting the National Strategy for Artificial Intelligence in 2019 and founding the Institute for Artificial Intelligence in 2021, Serbia laid strong foundations for the development of this technology. The introduction of AI in the educational system, the development of the research infrastructure and active participation in international initiatives have contributed to important results. Ethnical guidelines adopted in 2023 constitute the basis for accountable AI application. Being elected Chair of the Global Partnership on Artificial Intelligence for 2024 further confirms Serbia’s position. Continued support of the Government, educational institutions and the economic sector is crucial for the future development of AI technologies.